The export-productivity link for Brazilian manufacturing firms - Xavier Cirera; Daniel Lederman; Juan A. Má\~nez; María E. Rochina; Juan A. Sanchis (Kiel Institute for the World Economy (IfW), 2015)
This paper explores the link between exports and total factor productivity (TFP) for Brazilian manufacturing firms over the period 2000-2008, both under the assumption of an exogenous or an endogenous law of motion for productivity. The authors first obtain TFP estimates under each alternative assumption following Wooldridge (On estimating firm-level production functions using proxy variables to control for unobservables, 2009) GMM procedure. Second, using stochastic dominance techniques they analyse whether the ex-ante most productive firms are those that start exporting (self-selection hypothesis). Finally, the authors test whether exporting boosts firms TFP growth (learning-by-exporting hypothesis) using matching techniques, to control for the possibility that selection into exports may not be a random process. Their results confirm the self-selection hypothesis and show that starting to export yields firms an extra TFP growth that emerges since the first year exporting but lasts only from this year to the next. Further, this extra TFP growth is much higher under the assumption of an endogenous law of motion for productivity, which reinforces the importance of accounting for firm export status to study the evolution of productivity.
Keywords: F14; D24; C14; C33; C36; 330; TFP; export status; exogenous vs. endogenous Markov; semi-parametric approach; self-selection; stochastic dominance; learning-by exporting; matching techniques